Enhanced Electrosynthetic Hydrogen Evolution by Hydrogenases Embedded in a Redox‐Active Hydrogel. Issue 32 (11th May 2020) - Ruth, John C.; Milton, Ross D.; Gu, Wenyu; Spormann, Alfred M.
Abstract: Molecular hydrogen is a major high‐energy carrier for future energy technologies, if produced from renewable electrical energy. Hydrogenase enzymes offer a pathway for bioelectrochemically producing hydrogen that is advantageous over traditional platforms for hydrogen production because of low overpotentials and ambient operating temperature and pressure. However, electron delivery from the electrode surface to the enzyme's active site is often rate‐limiting. Here, it is shown that three different hydrogenases from Clostridium pasteurianum and Methanococcus maripaludis, when immobilized at a cathode in a cobaltocene‐functionalized polyallylamine (Cc‐PAA) redox polymer, mediate rapid and efficient hydrogen evolution. Furthermore, it is shown that Cc‐PAA‐mediated hydrogenases can operate at high faradaic efficiency (80–100 %) and low apparent overpotential (−0.578 to −0.593 V vs. SHE). Specific activities of these hydrogenases in the electrosynthetic Cc‐PAA assay were comparable to their respective activities in traditional methyl viologen assays, indicating that Cc‐PAA mediates electron transfer at high rates, to most of the embedded enzymes. Abstract : The redox polymer cobaltocene‐functionalized polyallylamine (Cc‐PAA) was utilized to immobilize hydrogenase enzyme on an electrode surface and mediate electron transfer for hydrogen evolution. Cc‐PAA has been found to effectively mediate electron transfer between an electrode and hydrogenases at high specificity and efficiency.